Estado da arte da obtenção de crédito de carbono via adoção de veículo elétrico - Ramos, Denis Fernando; dos Santos, Roni Robson; Grandinetti, Francisco José; Godoy Jr., Ederaldo [UNESP]; de Oliveira, Edson Aparecida de Araújo Querido (My University, 2012)
This paper aims to highlight the state of the art of obtaining carbon credits through the use of electric vehicles. This is one of the solutions to significantly reduce the emission of GHG (Greenhouse Gas) emissions in the case of CO 2, NOx, SOx, and CH 4 (thermochemical reactions arising from the combustion of gasoline with ethanol) in motor vehicles. For this quantitative study was done based on the survey of bibliographic data available and the development of basic calculations considering the car fleet of the Country of Brazil and the CO 2 emissions generated by the same. Thus explaining the considerable gain in air quality and reduction of vectors of greenhouse gases in the case of replacing the current fleet of vehicles combustion of hydrocarbon aliphatic chain, for an eco-efficient fleet consists of electric vehicles and/or hybrids.
State of the art of getting credit for the adoption of carbon electric vehicle
Keywords: Carbon credits; Electric; Greenhouse gases; VE; Vehicle